Analisis Nilai-Nilai Pendidikan Islam dalam Tradisi Mitoni Masyarakat Jawa Desa Bangun Rejo Kabupaten Solok Selatan - Puja Savira; Nurhasnah Nurhasnah; Fauzan Fauzan; Hamdi Abdul Karim (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by changes in the community that carries out the mitoni tradition. The mitoni tradition is a native tradition of Java pioneered by Hinduism and Buddhism, which used to be carried out in the Javanese or Kejawen way but has changed over time. This change is caused by the development of an increasingly modern era and the arrival of Islam to Indonesia. The changes that have occurred are about the elements of the ritual, from the original complete Kejawen ritual to a more spiritual tradition that has an Islamic feel without leaving the core of the tradition and the noble values contained. This research is a qualitative research that uses the type of field research and data collection using observation, interview and documentation methods. Then the analysis technique is through data reduction, data presentation and drawing conclusions. The informants in this research are the village head, religious leaders, traditional leaders and several people from Bangun Rejo Village, South Solok Regency. The results of this study indicate that in the implementation of the mitoni tradition there are several processions carried out during the day and night, where the processions carried out during the day are not all in accordance with Islamic teachings. Along with the development of an increasingly modern era, there have been many changes in the implementation of the mitoni tradition where some people only carry out the mitoni tradition by holding a simple kenduri and thanksgiving. The implementation of the mitoni tradition also contains Islamic educational values, namely the value of faith education in the form of sungkeman, brojolan, lawuhan, kenduri and kepungan processions. The value of worship education in the form of the siraman procession. The value of moral education in the form of a procession of sending prayers and reading the holy verses of the Qur’an. With the values of Islamic education that have developed in the mitoni tradition, the people of Bangun Rejo Village still maintain the mitoni tradition to this day.